Pengaruh Akuntabilitas Dan Transparansi Terhadap Efektivitas Pengelolaan Dana Bantuan Operasional Sekolah (BOS) Dengan Partisipasi Stakeholder Sebagai Variabel Moderasi - Rakhmawati, Ita (AKTSAR: Jurnal Akuntansi Syariah, 2018)
This study analyzes the effect of accountability and transparency on the effectiveness of BOS fund management with stakeholder participation as a moderating variable. The method used is moderation regression analysis with interaction test. The results showed that accountability has a positive and significant effect on the effectiveness of BOS fund management which is shown by t count equal to 2,701 significance level of 0,01 <0,05. While Transparency have negative and insignificant effect with t arithmetic equal to 1,642 and significance level 0,112> 0,05. Participation has positive and insignificant effect with t count 0,809 and significance level 0,423> 0,05. Participation has a negative and significant influence in moderating the relationship between accountability to the effectiveness of the management of BOS funds as indicated by the t count of 2.032 and the significance level of 0.048 <0.05. The participation of positive and significant influence in moderating the transparency relationship on the effectiveness of BOS fund management is shown by the t count for the transparency and participation interaction of 2.045 and the significance level of 0.047 <0.05.